Quality Control Analysis of Bored Pile Foundation Based on PDA Test and PIT Test - Yogaswara, Dendi; Riyantini, Ranti (Jurnal Teknik Sipil, 2025)
The bored pile foundation is an important structural element, which requires proper quality control, as it is constructed by casting on-site, so it is strongly influenced by soil conditions and the method of implementation. This research focuses on quality control in bored pile construction. The calculations using N-SPT data from Reese and Wright (1977) show that bored piles can hold 563.76 tonnes of weight at point BP103; 494.94 tonnes at point BP17; and 466.98 tonnes at point BH94. Using the Reese & O'Neil (1989) approach, the axial bearing capacity was 697.50 tonnes for point BH103; 738.53 tonnes for point BP17; and 497.34 tonnes for point BP94. This study also calculated the lateral resistance value using the Broms method, with a value of 56.58 tonnes depending on the stiffness of the pile. We also calculated the deformation analysis of the pile under load using the Vesic method, yielding a value of 0.020 m for a single bored pile, with a permissible settlement of 0.1 m. We used the dry drilling method to carry out the bored pile foundation work. Based on the PDA field test, the bearing capacity values for the piles are 863 tonnes, 880 tonnes, and 925 tonnes. The PDA test results indicate that the integrity of the bored piles in the field remains intact, indicating that the construction site's implementation aligns with the prepared plan.